Музей как место социальных связей. Фабрика Шиндлера в Кракове и Музей истории польских евреев По́лин в Варшаве - BOGUNIA-BOROWSKA, Małgorzata (Мониторинг общественного мнения: экономические и социальные перемены, 2016)
Museums are ambiguousspaces. On the one hand, they providesome models built on social perceptions,and on the other, they are places open tointerpretation. They are relational spaces.Spaces of various types of relations likeinstitutional, interpersonal, international,intergeneration or intercultural relations.They are also places of relations anddialogue, establishing and negotiatingmeanings. In any event, museums arealso, and perhaps above all, stories about people, events and the effects oftheir meetings.The article presents the results of qualitativeresearch devoted to the receptionof the museum, which was conductedin two museums the Museum of OskarSchindler’s Enamel Factory in Krakowand the Museum of the History of PolishJews POLIN in Warsaw. The project wastitled «My way, my choice». Special attentionis paid to the imaginative and relationalcharacter of the museum space.